Analysis of the metacognitive awareness inventory of students in the nursing technical course (Research, Society and Development, 2021)
This study aimed to obtain a diagnosis of the metacognitive perception of students from a technical nursing course, and to point out paths for autonomous learning. For that, an intersectional survey was carried out with 65 students of a technical course in nursing, during emergency remote teaching. The Metacognitive Awareness Inventory (MAI) was used to investigate the student's disposition in relation to their metacognitive knowledge and cognitive regulation, which implies the assessment of the ability to reflect and decision-making. 66% of metacognitive knowledge and 68% of regulation of cognition were observed. The first factor was composed of Conditional Knowledge (69%), Declarative (66%) and Procedural (62%). On the other hand, Cognition Regulation was distributed among Planning (68%), Information Management (69%), Monitoring (67%), Debugging (82%) and Evaluation (63%). Such results, among others, pointed to the need for improvement and expansion of metacognitive awareness, through the insertion of strategies to stimulate the culture of thinking, critical reflection, self-regulation of learning and learning to learn.